Conceptual framework for integrating BIM and augmented reality in construction management - Machado, Ricardo L.; Vilela, Cesar (Journal of Civil Engineering and Management, 2020)
The need for systematic data collection and processing to generate real-time building site progress information is critical. Building Information Modelling (BIM) provides the benefit of aggregating information about the building site on a single platform. Augmented reality (AR) emerges to enhance BIM concerning visualization of the building site, through processing and automatic absorption of information. This work aims to analyse the potential of AR association to BIM, by adopting an approach based on literature review. Trends in contemporary research are checked by categorizing applied research methods, areas of expertise, and AR technologies. Publications produced between 2008 and 2018 from journals of architecture, engineering, and construction areas in databases Web of Science, SciSearch, SCOPUS, INSPEC, Google Scholar, Academic OneFile, EBSCO, OCLC, VINITI, SCImago, and ProQuest were investigated. As main results, it was found that the case study approach was adopted in 41% of the publications analysed. The building site inspection was the research object in 48% of papers. Fiducial markers, GIS/GPS, laser scanners, and photogrammetry emerged as main options for automatic data capture on the progress of the building site. Integration between AR and BIM has the potential to solve information processing problems and improving construction management.